La cotidianidad del cuidado materno a niños hiperactivos - Castañeda Castañeda, Saidy Paola (2018)
This Qualitative research- Phenomenological Its purpose was to analyze comprehensively what is the daily care of mothers with hyperactive children , was developed at the I.E Warner School, in the District of Chepén, Province of Chepén, Department of the Libertad. The research subjects consisted by 8 young adults, mothers of children of school age selected by saturation of speeches. For the collection of data was used the in-depth interview, following the hermeneutical analysis technique for processing and analyzing them. As well as certain selection criteria. The findings we obtained were that the mothers' daily life is constant, Stressful and difficult to care for your hyperactive child. In this sense care is guided by the presence being launched, the dasein lives in concern occupation, cure-care, everydayness and facticity. According to the Heideggerian concepts.